2019
DOI: 10.1111/ajt.15197
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and pathological significance of borderline T cell–mediated rejection

Abstract: The pathological diagnosis of borderline rejection (BL‐R) denotes possible T cell–mediated rejection (TCMR), but its clinical significance is uncertain. This single‐center, cross‐sectional cohort study compared the functional and histological outcomes of consecutive BL‐R diagnoses (n = 146) against normal controls (n = 826) and acute TCMR (n = 55) from 551 renal transplant recipients. BL‐R was associated with the following: contemporaneous renal dysfunction, acute tubular necrosis, and chronic tubular atrophy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
104
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(107 citation statements)
references
References 39 publications
1
104
1
1
Order By: Relevance
“…In this regard, in a study aimed to explore the utility of the molecular diagnosis in indication biopsies displaying borderline changes, it was shown that most cases designated borderline by histopathology (67%) were found to be non-rejection by molecular phenotyping [41]. This finding is consistent with a clinical study in which borderline biopsies behaved as a very heterogenous group, ranging from mild non-progressive inflammation to overt TCMR [5]. These results suggest that some current Banff histopathology criteria may be unreliable, particularly at the cut-off between borderline changes and T-cell mediated rejection.…”
Section: Transcriptomes In Biopsies Categorized As Borderline Changessupporting
confidence: 76%
See 1 more Smart Citation
“…In this regard, in a study aimed to explore the utility of the molecular diagnosis in indication biopsies displaying borderline changes, it was shown that most cases designated borderline by histopathology (67%) were found to be non-rejection by molecular phenotyping [41]. This finding is consistent with a clinical study in which borderline biopsies behaved as a very heterogenous group, ranging from mild non-progressive inflammation to overt TCMR [5]. These results suggest that some current Banff histopathology criteria may be unreliable, particularly at the cut-off between borderline changes and T-cell mediated rejection.…”
Section: Transcriptomes In Biopsies Categorized As Borderline Changessupporting
confidence: 76%
“…The diagnosis of borderline changes in biopsies caused due to graft dysfunction leads to anti-rejection treatment with steroid pulses, while no treatment is given in most centers when this lesion is observed in surveillance biopsies. In a large clinic-pathological study conducted in more than 500 patients monitored with indication and surveillance biopsies, borderline changes emerged as a heterogeneous diagnostic group, ranging from mild inconsequential inflammation (resolved in about 60% of untreated cases) to clinically significant TCMR able to induce immune-mediated tubular injury [5].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, at Banff 2017, the criteria for tubulitis and interstitial inflammation were established as 't > 0 with i0 or i1' or 'i2 or i3 with t1' . In a recent report on borderline changes, these inconsistences have resulted in heterogeneous diagnostic groups [44].…”
Section: Criteria For Quantitative Scoringmentioning
confidence: 99%
“…TCMR 1A and borderline diagnoses often overlap; some borderlines behave as rejection and some TCMR do not. Borderline rejection is defined as changes on Banff histology that are not sufficient to diagnose rejection, yet Nankivell et al recently showed that borderline TCMR is associated with inferior graft outcomes despite resolution of inflammatory infiltrates on subsequent biopsies . Having a more quantitative method of assessing injury may complement histology and help to identify cases that require further intervention.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of this study is to test the hypothesis that TCMR 1A and borderline rejection are a heterogeneous cohort which may have variable impact on outcomes and that dd‐cfDNA may help to risk stratify patients and better differentiate which TCMR 1A or borderline cases may progress. Additionally, we aimed to consider the value of injury when assessing histopathology diagnoses described as active rejection, considering that the presence of inflammatory infiltrate is not always concurrent with active and ongoing cellular injury . We hypothesize the use of dd‐cfDNA as a complementary tool may support histopathology and potentially improve clinical decision‐making, when assessing whether the changes seen on histopathology are clinically significant …”
Section: Introductionmentioning
confidence: 99%